CHILDHOOD COUGH - RATIONAL APPROACH TO TREATMENT - I. M. Kosenko ("Paediatrician" Publishers LLC, 2013)
Questions of rational approach to treatment of childhood diseases accompanied by cough are discussed in this article. The author emphasized the necessity of taking into account special features of the disease, mechanisms of action of used drugs and their undesirable effects, as well as individual characteristics of a patient. High efficacy and safety of herbal drugs in treatment of respiratory disorders in children is shown. An algorithm of choice of drugs influencing on cough is offered.